Penyelenggaraan Festival Gandrung Sewu dan Pengelolaan Taman Gandrung Terakota Banyuwangi Sebagai Wisata Unggulan - Joko Triyono (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
The development of tourism in Banyuwangi Regency since 2003 was marked by the emergence of the Gandrung Dancer mascot which was later created by the Banyuwangi Terracotta Infatuated Park as a new icon of tourism which is quite instagenic in Banyuwangi. This paper seeks to explore the existence of the Terracotta Infatuated Park qualitatively descriptive with data sources from interviews, observation, and documentation, then supported by appropriate references to be analyzed with the 4A component namely Attractions, Accessibility, Amenities, and Activities to find out whether its existence is worthy of being used as an object featured tour. The results of the study indicate that the existence of the Terracotta Infatuated Park has been managed properly and deserves to be a leading tourist attraction. This object is unique because of the concept of arranging the statues of the Gandrung Dancer made of clay/pottery with its philosophical value. In addition to this, holding the Gandrung Sewu Festival as a tourist attraction has proven to be able to attract tourist visits when the festival is held, thereby increasing the welfare of the tourism community.